Developing 1-D velocity model along Matano Fault Zone, Sulawesi, Indonesia - Madona Madona; Mohammad Syamsu Rosid; Djati Handoko; Dimas Salomo Januarianto Sianipar (Diponegoro University Semarang Indonesia, 2026)
The Matano Fault, with a slip rate of 20 mm/year, is the most active strike-slip fault in Sulawesi after the Palu-Koro Fault. As a result, this region exhibits a high level of seismicity. Unfortunately, a number of studies that have been conducted only involve a less dense network of stations and global velocity models. This study aims to obtain an optimum velocity model using the VELEST program, which reliably represents the actual condition of the study area. The data used in this study consists of hypocenter, origin times, and P-wave arrival times from earthquakes (Mw ≥ 3), each containing at least six clearly identified P-wave phases. These data were obtained from 317 events that occurred within the region bounded by 120.10°E – 122.20°E and 2.99°S – 1.66°S during the period from January 2022 to March 2025. To determine the optimum 1-D velocity model, four initial models were tested, namely Koulakov, Arimuko, Crust, and Bunaga. These models were evaluated based on RMS, the stability test of the updated velocity model, uncertainty assessment using bootstrap test, and their consistency with previous studies. The evaluation results indicate that the Arimuko Model is the most reliable, as it provides the lowest RMS value, stable hypocenter relocations (±6–7 km), bootstrap results showing narrow uncertainty intervals, and consistency with earlier studies that identified a low-velocity zone at depths of 0–3 km. The result of this study is expected to serve as a reference for earthquake relocation and seismicity analysis at the Matano Fault Zone.